'Reason's Sympathy' and its Foundations in Productive Imagination. Issue 3 (11th September 2021) - Vilhauer, Benjamin
Abstract: This paper argues that Kant endorses a distinction between rational and natural sympathy, and it presents an interpretation of rational sympathy as a power of voluntary a posteriori productive imagination. In rational sympathy we draw on the imagination's voluntary powers (a) to subjectively unify the contents of intuition, in order to imaginatively put ourselves in others' places, and (b) to associate imagined intuitional contents with the concepts others use to convey their feelings, in such a way that those contents prompt feelings in us that are like their feelings.